Hubungan Media Sosial Instagram @Urban1063fm dalam Membangun Brand Image - Fauzan Haris Anavidi; Wiki Angga Wiksana (Jurnal Riset Manajemen Komunikasi, 2024)
Abstract. The rapid development of technology and information has become an inevitable necessity for society. One of its impacts is social media, which has become a key factor in marketing strategies and brand development, even for influential radio stations like Radio Urban 106.3 FM. This study explores the relationship between activities on the Instagram platform and the formation of Radio Urban 106.3 FM's brand image. A correlational analysis method was used with a quantitative approach, and the research population consisted of followers of Radio Urban 106.3 FM on Instagram. A total of 100 respondents were selected using Simple Random Sampling method. Data were collected through questionnaires and analyzed using descriptive and inferential techniques. The results of the study indicate a significant relationship between activities in context, communication, collaboration, and connection on Instagram with the formation of the brand image. The implication of this research underscores the importance of active presence of radio stations on social media to retain and attract listeners in a competitive digital era. This study contributes to a deeper understanding of the role of social media in radio station marketing strategies. Abstrak. Perkembangan teknologi dan informasi telah menjadi kebutuhan masyarakat yang tak terelakkan. Salah satu dampaknya adalah media sosial yang kini menjadi faktor kunci dalam strategi pemasaran dan pengembangan merek, bahkan bagi stasiun radio seperti Radio Urban 106,3 FM yang berpengaruh. Penelitian ini mengeksplorasi hubungan antara aktivitas di platform Instagram dengan pembentukan brand image Radio Urban 106,3 FM. Metode analisis korelasional digunakan dengan pendekatan kuantitatif, dan populasi penelitian adalah pengikut Radio Urban 106,3 FM di Instagram. Sebanyak 100 responden dipilih menggunakan metode Simple Random Sampling. Data dikumpulkan melalui kuesioner dan dianalisis menggunakan teknik deskriptif dan inferensial. Hasil penelitian menunjukkan adanya hubungan yang signifikan antara context, communication, collaboration, dan connection di Instagram dengan pembentukan brand image Implikasi penelitian ini adalah pentingnya kehadiran aktif stasiun radio di media sosial untuk mempertahankan dan menarik pendengar di era digital yang kompetitif. Penelitian ini memberikan kontribusi dalam pemahaman lebih lanjut tentang peran media sosial dalam strategi pemasaran stasiun radio.